Kinetic study of water transport in layered graphene oxide membranes. Issue 1 (1st January 2019) - Na, Meng; Zhao, Wang; Zhang, Xueyang
ABSTRACT: Layered graphene oxide (GO) membranes are considered promising separation membranes because of their lamellar structure, strong mechanical strength and strong hydrophilic properties. However, there are a limited number of studies on the mechanism of water transport through a layered GO membrane. In this paper, by using a self-synthesized layered GO membrane, we developed and validated the first dynamic equation to describe water transport through a layered GO membrane. The results showed that the relationship between membrane flux and GO loading is an exponential function and that the water flux decreases with increasing GO loading. Then, the dynamic equation was applied to previously reported layered GO membranes to further verify its applicability. This kinetic study on layered GO membranes provides insight into the development of high-performance membranes with high permeability and selectivity.